People of China's Economic Diplomacy Toward Japan 1949-1972 (Journal of the College of Education for Women, 2019)
Chinese policy was characterized in general toward Japan caution and fear and try tomobilize all energies and alliances possible in order to interact and deal with that neighborfoe, has that policy been in all its aspects to the enticements of regional and local conflicts, aswell as international variables that were the hardest and most influential on them.The importance of the choice of the People of China's economic diplomacy toward thestudy of Japan during the period of the Cold War is that each of them was in transition, Chinaat that time was barely beyond the midst of a civil war (1945-1949) led to the split into twostates: China, led by the People Mao Tse-Tung and Beijing as its capital, the National China(Taiwan), led by Chiang Kai-shek and the capital, Taipei, has been for each of these twocountries own ideology which constitutes the basis of international alliances and relationswith its neighbors, particularly Japan, the People's China once believed in the Communistideology and taken economically and politically, have a system, and it allied with the SovietUnion as the leader of that thought, while China took the national title of capitalist ideologyand its allied with its leader of the United States of America.As for Japan, the position was not less disruptive of China as they are also constrainedby international agreements imposed after losing in the Second World War in 1945, as well asthe United States control over the policy of internal and external that country, so Japan werenot free to choose friendships and economic cooperation with other countries.All These premises show the importance of popular economic diplomacy study ofChina to Japan during the period 1949-1972, since this study reflect a clear andcomprehensive picture of the visions and the Chinese trade in all its aspects during thatperiod, especially that of China followed a new style of politics, namely the use of theeconomic side as a means to achieve a political goal Fabtadt so the style and the military trendthat prevailed, as well as, the importance of the study of this subject at that time specifically isthat it is absent and a new page reveal at the same time of the Cold War pages were raging inthe continent of Asia, used the economic hub as a weapon new and important in that war.